PENGARUH PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP KONSENTRASI BELAJAR SISWA KELAS V DI SD NEGERI 165 PALEMBANG - Lathifah; Latifatuz Zahra; Sri Juwita; Donna Takrim; Sandrina Ramadhani; Febriyanti; Kurratulaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of TikTok social media usage on the learning concentration of fifth-grade students at SD Negeri 165 Palembang. This study uses a quantitative approach with an ex post facto research type. The sample in this study amounted to 20 students selected using a purposive sampling technique. Data collection techniques were carried out through questionnaires, observation, and documentation. The research instrument used a Likert scale of 1–4 which has been tested for validity and reliability. The data analysis technique used was simple linear regression with prerequisite tests in the form of normality and linearity tests. The results showed that all instruments were declared valid and reliable with a Cronbach's Alpha value of 0.926. The research data were also normally distributed and had a linear relationship. The results of the regression analysis showed that there was a significant effect between TikTok social media usage on student learning concentration, as indicated by a significance value smaller than 0.05. The direction of the resulting effect tended to be negative, which means that the higher the intensity of TikTok use, the lower the student's learning concentration. Based on these results, it can be concluded that TikTok social media usage affects student learning concentration. Therefore, supervision and control of social media usage are needed to prevent negative impacts on the learning process.